Intravesical Gentamicin: An Option for Therapy and Prophylaxis against Recurrent UTIs and Resistant Bacteria in Neurogenic Bladder Patients on Intermittent Catheterization - Elena Andretta; Raffaele Longo; Massimo Balladelli; Camilla Sgarabotto; Dino Sgarabotto (MDPI AG, 2022)
This is a retrospective study of our experience with Gentamicin intravesical instillation as therapy and prophylaxis in patients with lower urinary tract infections (UTIs) undergoing clean intermittent catheterization because of a neurogenic bladder. It is an alternative therapy when all other systemic treatments have failed as it is still an off-label prescription.